Perception And Compliance of Houseboat Fisherman Community in Lake Tempe in Utilizing Fishery Resources - Harmin Adijaya Putri; Sri Hardianti Rosadi; Zul Kariman (BUMI: International Journal of Environmental Reviews, 2023)
The Tempe Lake plays a crucial role in the livelihoods of the community, serving as a source of sustenance. The fisherman community of the floating house around Lake Tempe possesses distinct traditions and local wisdom in the utilization of fishery resources within the lake. This research aims to analyse the perceptions and compliance of the community regarding the utilization of fishery resources in Lake Tempe. The research is situated in the village of Pallimae, a community whose fishermen inhabit floating houses of Lake Tempe. Perceptions are assessed based on the understanding of the presence and utilization of fishery resources in Lake Tempe. Community compliance is evaluated in the management of freshwater fishery resources grounded in local wisdom values. Perceptions and compliance data were gathered through questionnaires and processed using regression analysis. The results of the perception and compliance tests indicate that the floating house fisherman community in Lake Tempe adheres to local wisdom values related to fisheries resource management, encompassing (1)Conceptual levels, including prohibitions against damaging the lake’s ecosystem; (2)Value-based behaviours, such as prohibitions against littering in the lake and refraining from using coarse language and arrogance; and (3)Cultural and customary practices, including the traditional Maccera tappareng ceremony.